Comparative Transcriptome Profiling Reveals Defense-Related Genes Against Ralstonia solanacearum Infection in Tobacco - Pan, Xiaoying; Chen, Junbiao; Yang, Aiguo; Yuan, Qinghua; Zhao, Weicai; Xu, Tingyu; Chen, Bowen; Ren, Min; Geng, Ruimei; Zong, Zhaohui; Ma, Zhuwen; Huang, Zhenrui; et al. (Frontiers in Plant Science, 2021)
Bacterial wilt (BW) caused by Ralstonia solanacearum (R. solanacearum), is a vascular disease affecting diverse solanaceous crops and causing tremendous damage to crop production. However, our knowledge of the mechanism underlying its resistance or susceptibility is very limited. In this study, we characterized the physiological differences and compared the defense-related transcriptomes of two tobacco varieties, 4411-3 (highly resistant, HR) and K326 (moderately resistant, MR), after R. solanacearum infection at 0, 10, and 17 days after inoculation (dpi). A total of 3967 differentially expressed genes (DEGs) were identified between the HR and MR genotypes under mock condition at three time points, including1395 up-regulated genes in the HR genotype and 2640 up-regulated genes in the MR genotype. Also, 6,233 and 21,541 DEGs were induced in the HR and MR genotypes after R. solanacearum infection, respectively. Furthermore, GO and KEGG analyses revealed that DEGs in the HR genotype were related to the cell wall, starch and sucrose metabolism, glutathione metabolism, ABC transporters, endocytosis, glycerolipid metabolism, and glycerophospholipid metabolism. The defense-related genes generally showed genotype-specific regulation and expression differences after R. solanacearum infection. In addition, genes related to auxin and ABA were dramatically up-regulated in the HR genotype. The contents of auxin and ABA in the MR genotype were significantly higher than those in the HR genotype after R. solanacearum infection, providing insight into the defense mechanisms of tobacco. Altogether, these results clarify the physiological and transcriptional regulation of R. solanacearum resistance infection in tobacco, and improve our understanding of the molecular mechanism underlying the plant-pathogen interaction.